Qualitative Study of Job Restrictions and Their Impact on the Performance and Earnings of Employees with Low Bargaining Power in Firm Resource Protection Strategies - Al Amin, Nuril Khusni; Santoso, Seger (International Journal of Business, Marketing, Economics & Leadership (IJBMEL), 2024)
This study aims to examine the impact of job restrictions on the performance and earnings of employees with low bargaining power, as well as the associated corporate resource protection strategies. Based on a qualitative literature review, it was found that job restrictions, such as non-competition agreements, can have negative effects on employees with low bargaining power, such as decreased job mobility, career stagnation, and lower earnings. However, some employees can experience benefits in the form of improved performance and development opportunities if provided with adequate support by the company. This study highlights the importance of companies to consider fair and transparent job restriction policies to minimize negative impacts on employees with low bargaining power